Evaluation of Self-Medication Practices and its Associated Factors among Urban Population of Ahmedabad City, Gujarat - Kapil J Govani; Khyati Nimavat (Medsci Publications, 2017)
Introduction: Self medication is an important issue for health authorities especially in developing countries like India. The study was conducted to assess the socio-demographic profile of urban population and also to assess the trend of self-medication practices & its associated factors. Methodology: A cross sectional study was conducted among urban population of central and north zone of Ahmedabad municipal Corporation (AMC) area during January to April 2015. Pretested performa was used for study. Among 250 houses, total 647 people were selected for study after their informed consent. Results: Out of 647 people, males were 54.3% & females were 45.7%. Majority of people were belongs to 25 to 35 yr. age group (27.2%). Majority of people were found in S-E class-3. Majority of male were used NSAIDS (74.6%) and female were used Anti emetics (81.8%) for self-medication practices. Most common influencing factor was media (37.9%) & pharmacist (41.9%) among upper & lower S-E class respectively. Conclusions: Mean age was 37.4 ± 2.6. Most common reason for self-medication was time constrains & high consulting fees of doctors among upper & lower S-E class respectively. Knowledge on different drug related reactions were shows significant different among both S-E classes (P: <0.0001).